Electric Vehicle Integration in a Smart Microgrid Environment - Alam, Mohammad Saad; Krishnamurthy, Malesh (CRC Press : Taylor & Francis Group, 2021)
The primary purpose of this book is to capture the state-of-the-art in smart microgrid management with EV integration and their applications. It also aims to identify potential research directions and technologies that will facilitate insight generation in various domains from smart home, industry, business, and consumer applications